The rs2294918 E434K variant modulates patatin‐like phospholipase domain‐containing 3 expression and liver damage. Issue 3 (14th January 2016) - Donati, Benedetta; Motta, Benedetta Maria; Pingitore, Piero; Meroni, Marica; Pietrelli, Alessandro; Alisi, Anna; Petta, Salvatore; Xing, Chao; Dongiovanni, Paola; del Menico, Benedetta; Rametta, Raffaela; Mancina, Rosellina Margherita; et al.
Abstract : The patatin‐like phosholipase domain‐containing 3 ( PNPLA3 ) rs738409 polymorphism (I148M) is a major determinant of hepatic fat and predisposes to the full spectrum of liver damage in nonalcoholic fatty liver disease (NAFLD). The aim of this study was to evaluate whether additional PNPLA3 coding variants contribute to NAFLD susceptibility, first in individuals with contrasting phenotypes (with early‐onset NAFLD vs. very low aminotransferases) and then in a large validation cohort. Rare PNPLA3 variants were not detected by sequencing coding regions and intron‐exon boundaries either in 142 patients with early‐onset NAFLD nor in 100 healthy individuals with alanine aminotransferase <22/20 IU/mL. Besides rs738409 I148M, the rs2294918 G>A polymorphism (E434K sequence variant) was over‐represented in NAFLD (adjusted P = 0.01). In 1, 447 subjects with and without NAFLD, the 148M‐434E ( P < 0.0001), but not the 148M‐434K, haplotype ( P > 0.9), was associated with histological NAFLD and steatohepatitis. Both the I148M ( P = 0.0002) and E434K variants ( P = 0.044) were associated with serum ALT levels, by interacting with each other, in that the 434K hampered the association with liver damage of the 148M allele ( P = 0.006). The E434K variant did not affect PNPLA3 enzymatic activity, but carriers of the rs2294918 A allele (434K) displayed lower hepatic PNPLA3 messenger RNA and protein levels ( P < 0.05). Conclusions: Rare loss‐of‐function PNPLA3 variants were not detected in early‐onset NAFLD. However, PNPLA3 rs2294918 E434K decreased PNPLA3 expression, lessening the effect of the I148M variant on the predisposition to steatosis and liver damage. This suggests that the PNPLA3 I148M variant has a codominant negative effect on triglycerides mobilization from lipid droplets, mediated by inhibition of other lipases. (Hepatology 2016;63:787–798)